Orbital cellulitis, sinusitis and intracranial abnormalities in two adolescents with COVID-19. (3rd July 2020) - Turbin, Roger E.; Wawrzusin, Peter J.; Sakla, Nicole M.; Traba, Christin M.; Wong, Kristin G.; Mirani, Neena; Eloy, Jean A.; Nimchinsky, Esther A.
ABSTRACT: We review two cases of adolescents with orbital cellulitis, sinusitis and SARS- CoV-2 infection presenting to emergency departments within a 24 hour period. SARS-CoV-2 samples obtained within 24 hours were positive, supporting prior infection despite relatively limited early symptoms of COVID-19. Unusual clinical and radiographic characteristics included hemorrhagic abscess with blood of varying age in the first, intracranial epidural abscess in the second, radiographic signal consistent with hemorrhagic or thrombotic phenomena, retro-maxillary antral fat changes, and meningeal enhancement or extension in both cases. Radiographic findings thereby mimic fungal infection, although final cultures and ancillary investigation for allergic and invasive fungal disease have remained negative. These cases highlight two unusual orbital presentations of cellulitis occurring in the context of SARS-CoV-2 co-infection.